Analisis Gender Dalam Hukum Islam - Ramli, Mohd Anuar (Jurnal Fiqh, 2012)
This article tends to discuss about gender analysis and its application in Islamic jurisprudence. This method of analysis emerged due to the change in social structure that formed the pattern of social relations nowadays that are totally different from the traditional social relation. In accordance to this, there are also the emergence of gender discriminations in Muslims? societies nowadays. Among the criteria that are being utilised in this type of analysis such as the differentiation between the concept of sex and gender, the identification of the existence of several elements in gender relationship such as marginalization, subordination, double burden, gender stereotype, sexual harassment, and gender-violence based. This research shows that gender analysis is a relevant mechanism to be applied in evaluating gender relation in Islamic rulings. However, it still need to be based on the value of justice and fairness. This is due to the fact that, not all differences among genders in the perspectives of gender analysis imply gender injustice. Therefore, gender justice could be obtained by putting an element in its proper place and function.